Role of the nurse in the care of the newborn in rooming-in care: an integrative review (Research, Society and Development, 2021)
The present study is a bibliographic research with a qualitative approach carried out by the integrative review method and which involves systematization, whose objective is to identify what the scientific literature has pointed out regarding the Nurse's Performance in relation to the care of newborns in rooming-in. For data search, online research platforms, Virtual Health Library in the following databases were used as collection sources: Latin American and Caribbean Health Sciences Literature, Nursing Database, Medical Literature Analysis and Retrievel System Online, by crossing the following descriptors, according to the Health Sciences Descriptors: "Newborn", "Joint Housing", "Nursing Care", articulated to the Boolean operator "AND", integrating the inclusion criteria and exclusion. From this withdrawal, a final sample of 15 articles was contemplated. Through the critical and interpretive analysis of the studies, two categories were created that allowed synthesizing the findings: “Nurse's Guidelines for mothers who have recently given birth and/or family members in relation to Breastfeeding” and “Educational practices performed by nurses in routine care procedures to the newborns in the Rooming-in”. It is concluded that most of the articles in this review highlighted the importance of breastfeeding for a good development and growth of the NB and, in general, the analyzed studies pointed to the importance of health education in rooming-in. The studies in this review brought important contributions to the care provided by the Nurse regarding the assistance provided to the NB in ​​Rooming-in.